What, How, and Why? A Comparative Analysis of 12 Goal-Free Evaluations - Brandon W. Youker (Journal of MultiDisciplinary Evaluation)
Background: Goal-free evaluation (GFE) is any evaluation in which the evaluator conducts the evaluation without reference to predetermined goals or objectives.